P-Coumaric acid attenuates alcohol exposed hepatic injury through MAPKs, apoptosis and Nrf2 signaling in experimental models. (25th April 2020) - Sabitha, Ramakrishnan; Nishi, Kumari; Gunasekaran, Vinoth Prasanna; Agilan, Balupillai; David, Ernest; Annamalai, Govindhan; Vinothkumar, Rajamanickam; Perumal, Malliga; Subbiah, Latha; Ganeshan, Mathan
Abstract: Overconsumption of alcohol could lead to severe liver injury that connects with oxidative stress, apoptosis, and inflammatory response. Previously, we proved that p-coumaric acid prevents ethanol induced reproductive toxicity; however, p-coumaric acid (PCA) on ethanol mediated hepatotoxicity has not been examined yet. In our work, we sought to study the potential of PCA in contradiction of ethanol induced hepatoxicity which linking with MAPKs, apoptosis, oxidative stress, and Nrf2 signaling. Foremost, we found that PCA could protect ethanol induced both L-02 and HepG2 hepatic cells by inhibiting cytotoxicity, ROS production, mitochondrial depolarization, and nuclear fragmentation. Also, in vivo experiments showed that the ethanol increasing the lipid markers (TBARS, CD) and depletes the antioxidants thereby increased phosphorylation of JNK, ERK, and p38 in rat liver tissues. Interestingly, PCA treatments inhibit ethanol exposed lipid markers and depletion of antioxidants, which directs the inhibition of MAPKs activation in rat liver tissues. We also noticed that the PCA protected ethanol induced apoptosis and liver markers by inhibiting the expression of Bax, caspases; AST, ALT, ALS, and LDH in liver tissue. Overall, the ameliorative consequence of PCA on ethanol induced oxidative stress and apoptosis was achieved by suppressing the expression of CYP2E1 and overexpressing Nrf2 and its target protein HO-1 in rat liver tissue. As a result, PCA was marked to be an effective antioxidant with notable hepatoprotection by inhibiting MAPKs and apoptosis signaling via enhancing Nrf2 signaling. Highlights: PCA protects alcohol induced both L-02 and HepG2 hepatic cells. PCA attenuates ethanol induced oxidative stress by inhibiting MAPKs. PCA also regulates liver regulating biomarkers and antioxidants. PCA prevents alcohol induced apoptosis and depletion of Nrf2 related proteins. PCA can be considered as alternative therapeutics for alcohol related disease.